Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.413
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-Linguistic Question Answering (VLQA) Challenge

Abstract: Understanding images and text together is an important aspect of cognition and building advanced Artificial Intelligence (AI) systems. As a community, we have achieved good benchmarks over language and vision domains separately, however joint reasoning is still a challenge for state-of-the-art computer vision and natural language processing (NLP) systems. We propose a novel task to derive joint inference about a given image-text modality and compile the Visuo-Linguistic Question Answering (VLQA) challenge corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Knowledge-based visual question answering (Wang et al, 2017(Wang et al, , 2018Marino et al, 2019;Sampat et al, 2020) proposed benchmark datasets for knowledge-based visual question answering that requires reasoning about an image on the basis of facts from a large-scale knowledge base (KB) such as Freebase (Bollacker et al, 2008) or DBPedia (Auer et al, 2007). To solve the task, two pioneering studies (Wang et al, 2017(Wang et al, , 2018 suggested logical parsing-based methods which convert a question to a KB logic query using predefined query templates and execute the generated query on KB for searching an answer.…”
Section: Related Workmentioning
confidence: 99%
“…Knowledge-based visual question answering (Wang et al, 2017(Wang et al, , 2018Marino et al, 2019;Sampat et al, 2020) proposed benchmark datasets for knowledge-based visual question answering that requires reasoning about an image on the basis of facts from a large-scale knowledge base (KB) such as Freebase (Bollacker et al, 2008) or DBPedia (Auer et al, 2007). To solve the task, two pioneering studies (Wang et al, 2017(Wang et al, , 2018 suggested logical parsing-based methods which convert a question to a KB logic query using predefined query templates and execute the generated query on KB for searching an answer.…”
Section: Related Workmentioning
confidence: 99%
“…Scientific problem solving has recently been employed to evaluate the multi-hop reasoning capability and interpretability of AI systems (Kembhavi et al 2017;Sampat, Yang, and Baral 2020;Dalvi et al 2021). However, these datasets (Kembhavi et al 2017;Jansen et al 2018) suffer from limited scale.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific problem solving has recently been employed to evaluate the multi-hop reasoning capability and interpretability of AI systems [6,12,28]. However, these datasets [11,12] suffer from limited scale.…”
Section: Introductionmentioning
confidence: 99%